Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Connect with a community of experts ready to help you find solutions to your questions quickly and accurately. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

Q2: A curve is given parametrically by the equations

[tex]\[ x = 1 - \cos 2\theta, \quad y = \sin 2\theta, \quad 0 \leq \theta \ \textless \ 2\pi \][/tex]

The point [tex]\( P \)[/tex] lies on this curve, and the value of [tex]\(\theta\)[/tex] at [tex]\( P \)[/tex] is [tex]\(\frac{\pi}{6}\)[/tex]. Show that an equation of the normal to the curve at [tex]\( P \)[/tex] is given by

[tex]\[ y + \sqrt{3}x = \sqrt{3} \][/tex]


Sagot :

Let's start by finding the coordinates of the point [tex]\(P\)[/tex] on the curve where [tex]\(\theta = \frac{\pi}{6}\)[/tex].

Given the parametric equations:
[tex]\[ x = 1 - \cos 2\theta \][/tex]
[tex]\[ y = \sin 2\theta \][/tex]

When [tex]\(\theta = \frac{\pi}{6}\)[/tex]:
[tex]\[ x_P = 1 - \cos\left(2 \cdot \frac{\pi}{6}\right) = 1 - \cos\left(\frac{\pi}{3}\right) \][/tex]
[tex]\[ y_P = \sin\left(2 \cdot \frac{\pi}{6}\right) = \sin\left(\frac{\pi}{3}\right) \][/tex]

We know that:
[tex]\[ \cos\left(\frac{\pi}{3}\right) = \frac{1}{2} \][/tex]
[tex]\[ \sin\left(\frac{\pi}{3}\right) = \frac{\sqrt{3}}{2} \][/tex]

Thus, the coordinates of point [tex]\(P\)[/tex] are:
[tex]\[ x_P = 1 - \frac{1}{2} = \frac{1}{2} \][/tex]
[tex]\[ y_P = \frac{\sqrt{3}}{2} \][/tex]

Next, we will determine the slope of the tangent line at point [tex]\(P\)[/tex]. For that, we need to find the derivatives [tex]\(\frac{dx}{d\theta}\)[/tex] and [tex]\(\frac{dy}{d\theta}\)[/tex].

Given:
[tex]\[ x = 1 - \cos 2\theta \][/tex]
[tex]\[ y = \sin 2\theta \][/tex]

The derivatives are:
[tex]\[ \frac{dx}{d\theta} = \frac{d}{d\theta}(1 - \cos 2\theta) = 2 \sin 2\theta \][/tex]
[tex]\[ \frac{dy}{d\theta} = \frac{d}{d\theta}(\sin 2\theta) = 2 \cos 2\theta \][/tex]

At [tex]\(\theta = \frac{\pi}{6}\)[/tex]:
[tex]\[ \frac{dx}{d\theta} \bigg|_{\theta = \frac{\pi}{6}} = 2 \sin\left(2 \cdot \frac{\pi}{6}\right) = 2 \sin\left(\frac{\pi}{3}\right) = 2 \cdot \frac{\sqrt{3}}{2} = \sqrt{3} \][/tex]
[tex]\[ \frac{dy}{d\theta} \bigg|_{\theta = \frac{\pi}{6}} = 2 \cos\left(2 \cdot \frac{\pi}{6}\right) = 2 \cos\left(\frac{\pi}{3}\right) = 2 \cdot \frac{1}{2} = 1 \][/tex]

The slope of the tangent line at [tex]\(P\)[/tex] is given by:
[tex]\[ \text{slope of tangent} = \frac{\frac{dy}{d\theta}}{\frac{dx}{d\theta}} = \frac{1}{\sqrt{3}} \][/tex]

The slope of the normal line is the negative reciprocal of the slope of the tangent line:
[tex]\[ \text{slope of normal} = -\frac{1}{\frac{1}{\sqrt{3}}} = -\sqrt{3} \][/tex]

We can now write the equation of the normal line in point-slope form:
[tex]\[ y - y_P = \text{slope of normal} \times (x - x_P) \][/tex]
[tex]\[ y - \frac{\sqrt{3}}{2} = -\sqrt{3}(x - \frac{1}{2}) \][/tex]

Rearranging to get it in the form of [tex]\(y = mx + b\)[/tex]:
[tex]\[ y - \frac{\sqrt{3}}{2} = -\sqrt{3}x + \frac{\sqrt{3}}{2} \][/tex]
[tex]\[ y = -\sqrt{3}x + \frac{\sqrt{3}}{2} + \frac{\sqrt{3}}{2} \][/tex]
[tex]\[ y = -\sqrt{3}x + \sqrt{3} \][/tex]

Adding [tex]\(\sqrt{3}x\)[/tex] to both sides to get it in the desired format:
[tex]\[ y + \sqrt{3}x = \sqrt{3} \][/tex]

Therefore, the equation of the normal to the curve at [tex]\(P\)[/tex] is:
[tex]\[ y + \sqrt{3}x = \sqrt{3} \][/tex]
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.